Post Fire Behavior of Structural Reinforced Concrete Member (Slab) Repairing with Various Materials - Asser Elsheikh; Hadeal H. Alzamili (Civil Engineering Journal, 2023)
One of the most significant building materials used to build a variety of infrastructure, military, and civil structures is concrete. It can effectively withstand fire mishaps for a long period of time. This study employs a finite element simulation approach in Three steps: the first involves applying mechanical loading, the second involves applying mechanical and thermal loading; and the third involves strengthening the damaged model. Two different strengthening procedures were used to evaluate the performance of the fire-damaged slab. Two types of strengthening techniques—carbon-fiber-reinforced polymer (CFRP) sheet and slurry-infiltrated fibrous concrete (SIFCON) jacketing—were used. Studying the performance of SIFCON and CFRP together and in two different thicknesses of each for repairing both normal and high-strength concretes after fire exposure is considered limited. An investigation of their behavior can provide insights into how effective the restoration of strength is. The study aims to assess how well various repair materials perform in restoring the durability and strength of reinforced concrete members after being exposed to fire. This will assist in determining the best materials for concrete repair after a fire. Results show that the enhancements by SIFCON with a thickness of 30 mm significantly improved many indices, including load displacement behavior, ductility, and absorption energy of the slab. Doi: 10.28991/CEJ-2023-09-08-013 Full Text: PDF